Green rider - Britain, Kristen (Britain, Kristen. Green rider (Series), 2008)
Heading home from school, Karigan G'ladheon encounters a dying "Green Rider", one of the king's messengers, who begs her to complete his mission. She reluctantly agrees and finds herself caught in a world of dangerous magic and even more dangerous enemies.